Pemanfaatan Pemasaran Digital: Meningkatkan Potensi Ekspor Briket Arang Tempurung Kelapa dalam Bisnis Internasional - Phung, Cavin Kleinsteuber; Wikartika, Ira (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is a study of the role of digital marketing for the export of Indonesian coconut shell charcoal briquettes, as a means of marketing to the global market. This coconut shell charcoal product is one of Indonesia's prima donna commodities, due to the quality of coconuts that grow in Indonesia. However, in carrying out export activities, of course, actors need to spend extra effort in marketing and selling to the global market. For this reason, this research, which uses a qualitative literature study method, aims to tell what steps businesses can take in utilizing digital marketing. The results of this study reveal the convenience gained by maximizing digital features to reach an effective and efficient international market. Keywords: Export, Briquette, Japan, South Korea, Digital Marketing.